Pemanfaatan Media YouTube KABI untuk Pembelajaran Materi Sirah Nabawiyah Guna Meningkatkan Motivasi Belajar - Sri Wahyuni; Martin Kustati; Gusmirawati, Gusmirawati (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
The learning process that engages students greatly influences their interest in learning. The integration of technology in education can enhance students’ interest and motivation to learn, and technological advancements provide significant support in delivering education on Islamic religious knowledge. Various social media platforms can serve as learning resources. With technological assistance, it becomes easier to spread religious knowledge in innovative and creative ways. This technology can also capture students’ attention, as it enables the creation of animated videos to enhance students’ comprehension of religious knowledge. An example of such a platform that can serve as an educational resource is YouTube Kabi. YouTube Kabi is an interactive medium that offers engaging audio-visual content with animations that capture students’ interest. The delivery of Sirah Nabawiyah material can be accomplished easily because this application can be accessed on laptops or smartphones. The purpose of this study is to examine the utilization of YouTube Kabi in teaching Sirah Nabawiyah material. The method employed in this study is qualitative with a descriptive approach. This research is field-based, and the data collection process involves observation, interviews, and documentation. The findings of this study demonstrate that YouTube Kabi serves as an example of an Islamic educational resource that can enhance students’ motivation to learn, especially in learning Sirah Nabawiyah material, because during the learning process, students demonstrate enthusiasm and engagement.